Reconstruction of Electronic Textbooks (E-Books) Assisted by Flip Pdf Professional on Optical Instruments - Suci Prihatiningtyas; Kartika Wulandari; Ino Angga Putra; Novia Ayu Sekar Pertiwi; Mujib Riduwan (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2023)
The research aimed to produce professional flip pdf-assisted electronic textbooks (e-books) and to find out the feasibility, as well as the user's response to the material for optical instruments. This type of research is development research and development (R&D) with the ADDIE model. The research subjects totaled 34 respondents consisting of class XI MIPA students and physics students. The research instrument used was the validator's assessment sheet regarding material and media aspects as well as a respondent's questionnaire regarding the use of e-books filled out via Google Forms. The results of the data analysis resulted in a product in the form of an electronic textbook (e-book) assisted by professional flip pdf materials on optical instruments which can be accessed using a PC and smartphone. The results of the validation of material and media experts obtained an average validation score of 81.0% which indicates the overall valid and feasible criteria of the e-book produced. Positive responses from users obtained an average percentage of 88.6% with a very good predicate. This means that the professionally developed flip pdf-assisted e-book is feasible and interesting for users to use in learning optical instruments in class X MIPA.